Implementation of Appsheet-Based Queue Management at Public Electric Vehicle Charging Stations SPKLU - Muhammad Ridhan Fadli Rahman; Dian Permata Sari (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
A significant increase in electric adoption in Indonesia has created high demand at public electric vehicle charging stations (SPKLU). Reliance on manual queue management methods at these stations often results in vehicular congestion and unstructured recording processes. This study implements and evaluates "Antridaya," an application designed to streamline queue recording at SPKLUs, developed using the AppSheet platform. Employing a prototyping methodology, the research conducted two testing phases: functional validation by five experts across 32 system components and a feasibility assessment using the System Usability Scale (SUS) with 21 SPKLU officers. The results indicate that Antridaya is functionally valid, securing an average score of 3.9 on a 4.0 scale. Moreover, the system demonstrated high end-user feasibility with an average SUS score of 85.7. This score stability was confirmed via a 95% confidence interval (78.63–92.79), placing the application in the "acceptable" category with an "excellent" rating. This study confirms that AppSheet provides a viable solution for digitizing queuing processes, offering a valid, user-friendly tool that establishes a foundation for standardized data recording systems.